Digestibility, metabolic utilisation and effects on growth and slaughter traits of diets containing whole plant maize silage in heavy pigs. Issue 1 (2nd January 2017) - Galassi, Gianluca; Malagutti, Luca; Rapetti, Luca; Crovetto, Gianni Matteo; Zanfi, Cristina; Capraro, Diego; Spanghero, Mauro
Abstract: Two experiments were conducted to investigate the inclusion of high cut whole plant corn silage (HCCS) in diets for finishing heavy pigs on digestibility, metabolic utilisation, growth performance and slaughter traits. A control diet (CTR, containing maize meal, barley meal, extracted soybean meal and wheat bran, 550, 250, 90 and 80 g/kg DM, respectively) was compared with diet (CS) containing 200 g/kg DM of HCCS. The HCCS replaced wheat bran and part of maize meal in the CTR diet. In the first experiment, eight barrows were used in a two periods cross over design with periods of 21 d, included 7 d of total collection and three cycles of 24 h each in a respiratory chamber. In the second experiment, 28 barrows were divided into pairs on the basis of BW, kept in 14 pens and fed with the experimental diets until slaughter. Lower DM, OM, CP and energy total tract apparent digestibility was measured for the CS diet. Overall P retention as percentage of P intake was higher for CS diet, while N retention was similar for the two diets. Pigs fed CS tended to have a lower retained energy and the estimated NE of maize silage was 8.47 MJ/kg DM. Pigs fed the CS diets had a lower daily gain, a lower BW at slaughter and a reduction in the weight of back fat. The inclusion of HCCS increased the size of the stomach, the aNDFom concentration of stomach content and reduced the incidence of follicular gastritis.